The model of goods delivery using multi depot vehicle routing problem at PT X - Sulistyono, Eko; Handayani, Vitri Aprilla; Reza, Widya; Islamiati, Dian (Universitas Islam Negeri Raden Intan Lampung, 2023)
Vehicle Routing Problem (VRP) is a problem in shipping that focuses on distributing goods from a depot to customers. There are several developments from VRP, one of which is the Multi Depot Vehicle Routing Problem (MDVRP). The MDVRP model has the same goal as the VRP, which is to minimize travel costs. The difference between VRP and MDVRP depends on the depot used. In VRP, only one depot is used. Whereas in MDVRP, there is more than one depot used. This research discussed the delivery of goods to two depots. The aim of this research is to form a model for shipping goods using two depots, determine the total travel cost, and determine the optimal route to delivery of the goods. The data used in this research is secondary data. The result of this research is that the model for the MDVRP aims to minimize the total travel cost by using two depots and serving 10 customer locations. The total cost of the trip is IDR 390,000, with a total distance traveled as far as 300 km, and the optimal routes for delivering goods involve each depot making two trips. The first depot covers distances of 57 km and 48 km, and the second depot covers distances of 92 km and 103 km.